Diffusion kinetics of water in graphite anodes for Li-ion batteries. Issue 6 (2nd May 2022) - Eser, Jochen C.; Deichmann, Birthe; Wirsching, Tobias; Merklein, Lisa; Müller, Marcus; Scharfer, Philip; Schabel, Wilhelm
Abstract: Since the loading of electrodes for Li-ion batteries with an excessive amount of moisture affects the performance of the cells, the moisture is partly removed in a post-drying process step. The drying time is thereby controlled by the amount of moisture that has to be removed as well as the mass transport kinetics of water. This mass transport kinetics is limited by various mass transport resistances, which in turn can be influenced by individual dryer settings. In this paper, we investigate water-based anodes for Li-ion batteries as well as selected materials, and distinguish between different possible mass transport resistances that affect the drying time. Determined diffusion coefficients can be used in future modeling of the post-drying process. Special consideration needs to be bestowed upon the mass transport of water in the polymeric binders, since earlier investigations revealed that the moisture uptake of the anodes is particularly caused by sodium carboxymethyl cellulose (Na-CMC). This high water uptake by the binder in water-based electrodes leads to a polymer film drying process within the porous structure of the electrode. The diffusion of water in layers of binder is particularly dependent on the concentration as well as the temperature of the binder.